2021
DOI: 10.1088/1755-1315/624/1/012155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potato tubers of Nevsky variety and selection hybrids by amino acid composition

Abstract: Potato protein is recognized as one of the most valuable plant proteins due to its high content of essential amino acids. Changes in the metabolic composition of potato tubers during low temperature storage can affect their nutritional value. In the course of study, the amino acid composition of potato tubers was determined, differing in the color of the pulp stored at a temperature of 2 °C for 7 months. The research included the study of 3 hybrids of potato and potato variety of standard Nevsky, hybrid 10.76.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Although the percentage of protein in potatoes is relatively low (0.7-4.6%), it may contribute to the protein intake due to the large amount consumed. Potato protein contains 18 amino acids, including the essential 9: tryptophan, leucine, isoleucine, valine, threonine, lysine, methionine, phenylalanine, and histidine [66]. In a previous study, it was observed that they represent around 25% of the total amino acid, with valine being the one with the highest presence (with 5.3% of the total amino acid), followed by lysine (4.5%) and leucine (4.3%).…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the percentage of protein in potatoes is relatively low (0.7-4.6%), it may contribute to the protein intake due to the large amount consumed. Potato protein contains 18 amino acids, including the essential 9: tryptophan, leucine, isoleucine, valine, threonine, lysine, methionine, phenylalanine, and histidine [66]. In a previous study, it was observed that they represent around 25% of the total amino acid, with valine being the one with the highest presence (with 5.3% of the total amino acid), followed by lysine (4.5%) and leucine (4.3%).…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
“…There are different human and natural factors that could affect the content and composition of the amino acids present in potatoes. Knowing this content is important as amino acids indirectly affect the taste (due to aspects such as the ratio of amino acids to sugars or starch content) and the aromatic properties of potatoes [66]. Among human factors, it was shown that the exogenous amino acid content was higher when the nitrogen fertilization level was lower [64].…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Например, в Челябинской области в 90-е годы ХХ века продуктивность картофеля составляла в среднем 9,2 т/га, в первом десятилетии XXI века -13,5 т/га, во втором -16,2 т/га. С одной стороны, 76-процентный рост урожайности, а с другой -даже последний показатель в 2,5-3 раза ниже, чем в Германии или Нидерландах [2]. Важным резервом увеличения эффективности картофелеводства является создание адаптивных сортов, высокий потенциал урожайности которых сочетается с пластичностью и высокой устойчивостью к основным биогенным и абиогенным стрессовым факторам [3][4][5][6][7][8][9].…”
Section: постановка проблемы (Introduction)unclassified
“…Методология Объектом исследований являлись 13 сортов картофеля белорусской селекции (Архидея, Бриз, Зорачка, Криница, Лад, Лилея Белорусская, Манифест, Скарб, Палац, Першацвет, Уладар, Явар, Янка), 10 -челябинской (Агат, Амулет, Губернатор, Захар, Ицил, Кавалер, Каштак, Краснопольский, Кузовок, Тарасов), 4 -свердловской (Барон, Ирбитский, Каменский, Лидер), 3 сорта-стандарта: Удача (ранний), Невский (среднеранний), Спиридон (среднеспелый), а также 6 сортов иностранной селекции, преобладающие в сельхозпредприятиях Челябинской области: Розара (доля его в сортовой структуре -27,6 %), Ред Скарлетт (25,9 %), Ароза (7,1 %), Королева Анна (6,2 %) -ранние, Гала (12,6 %) и Зекура (5,7 %) -среднеранние [2].…”
Section: постановка проблемы (Introduction)unclassified